A "Multi‐Heavy‐Atom" Approach toward Biphotonic Photosensitizers with Improved Singlet‐Oxygen Generation Properties. Issue 38 (30th May 2019) - Galland, Margaux; Le Bahers, Tangui; Banyasz, Akos; Lascoux, Noëlle; Duperray, Alain; Grichine, Alexei; Tripier, Raphaël; Guyot, Yannick; Maynadier, Marie; Nguyen, Christophe; Gary‐Bobo, Magali; Andraud, Chantal; et al.
Abstract: Two trispicolinate 1, 4, 7‐triazacyclonane (TACN)‐based ligands bearing three picolinate biphotonic antennae were synthetized and their Yb 3+ and Gd 3+ complexes isolated. One series differs from the other by the absence (L 1 )/presence (L 2 ) of bromine atoms on the antenna backbone, offering respectively improved optical and singlet‐oxygen generation properties. Photophysical properties of the ligands, complexes and micellar Pluronic suspensions were investigated. Complexes exhibit high two‐photon absorption cross‐section combined either with NIR emission (Yb) or excellent 1 O2 generation (Gd). The very large intersystem crossing efficiency induced by the combination of bromine atom and heavy rare‐earth element was corroborated with theoretical calculations. The 1 O2 generation properties of L 2 Gd micellar suspension under two‐photon activation leads to tumour cell death, suggesting the potential of such structures for theranostic applications. Abstract : In a flash : Trispicolinate 1, 4, 7‐triazacyclonane‐based gadolinium complexes exhibits high two‐photon absorption cross‐section combined with near‐unity 1 O2 generation. The very large intersystem crossing efficiency induced by the combination of bromine atoms and heavy rare‐earth elements was corroborated with theoretical calculations. The 1 O2 generation properties of micellar suspensions under two‐photon activation led to tumour cell death, suggesting the potential of such structures for theranostic applications.